1,3-Dimesitylimidazolidinium tetrachloridogold(III) dichloromethane solvate - Hagos, Tesfamariam K. (International Union of Crystallography, 2008)
The title ionic compound, (C(21)H(27)N(2))[AuCl(4)]·CH(2)Cl(2), was obtained from the reaction of 1,3-dimesitylimidazolidinium chloride with t-BuOK and a solution of AuCl(3) in tetrahydrofuran. In the crystal structure, numerous weak C—H⋯Cl hydrogen bonds form double layers parallel to (100), which are further stabilized by π–π interactions between mesitylene rings [centroid–centroid distance = 4.308 (4) Å], resulting in the formation of a three-dimensional supramolecular assembly.